Sembène's Progeny: A New Trend in the Senegalese Novel - Albert Gérard; Jeannine Laurent (Studies in 20th & 21st Century Literature, 1980)
The growth of the Nouvelles Editions Africaines in Senegal has proved favorable to the promotion of a national literature whose grass-roots inspiration is in obvious reaction against the elitist proclivities of earlier writers trained in French universities. The younger novelists follow in the footsteps of Sembène Ousmane, depicting actual living conditions among the under-privileged and usually silent majority in present-day Dakar. Recent examples are Aminata Sow Fall's La Grève des battù (1979), Moussa Ly Sangaré's Sourd-muet, je demande la parole (1978) and Mariama Bâ's Une si longue lettre (1979). Such works are designed for a local readership, which is numerous enough because Senegal has the highest rate of literacy in French of all African countries. While the clinical realism of their narrative technique is similar to Sembène's in many respects, the characteristic feature of those writers is that they do not seem to have any political axe to grind: their detached lucidity and absence of bitterness makes their image of the African megalopolis all the more impressive and depressing.
Keywords: Nouvelles Editions Africaines; Senegal; Sembène Ousmane; Dakar; Aminata Sow Fall; La Grève des battù; Moussa Ly Sangaré; " Sourd-muet; je demande la parole" Mariama Bâ; Une si longue lettre; literacy; megalopolis; Africa